انجاز وتصميم موقع للتوظيف العمومي - غزال نرجس** قريشة ملاك**تومي يسرى (university of eloued جامعة الوادي, 2024)
واجة تسيير نظام التسجيل الأولى في مسابقات التوظيف العمومي خلال السنوت الماضية العديد من التحديات و المعيقات التي اثرت سلبا على سير العمل في الإدارة , شملت هذه التحديات صعوبات في متابعة و التسيير و التقييم مما أدى الى تعقيدات إدارية و زيادة في الهد المبذول . لذلك, وحرصا على تسهيل عمل الادارة في تسيير عملية لتسجيل في المسابقات الالكترونية , ظهرت الحاجة الى انشاء موقع الكتروني مخصص , سيساهم هذا الموقع في الابتعاد ن الطرق التقليدية المجهدة و يساعد على تبسيط الإجراءات و تحسين كفاءة العمل Over the past years, the management of the initial registration system in public employment competitions has faced many challenges and obstacles that have negatively affected the workflow of the administration. These challenges included difficulties in monitoring, management and evaluation, which led to administrative complications and an increase in the effort expended. Therefore, in order to facilitate the administration’s work in managing the registration process for electronic competitions, the need arose to create a dedicated website. This website will contribute to moving away from stressful traditional methods, help simplify procedures and improve work efficiency.
مدكرة ليسانس اعلام الي
Keywords: توظيف عمومي ، المترشح، المسابقة; public employment; candidate; competition